DEVELOPING A BILINGUAL PROMOTIONAL BOOKLET AND WEBSITE FOR WISATA AGRO WONOSARI IN MALANG - Farida Insani Khairunissa Gunawan (Jurnal Linguistik Terapan, 2023)
Wisata Agro Wonosari is one of the agro-tourism places with tea gardens located in one of the districts in Malang, namely Lawang. Wisata Agro Wonosari has very superior potential with the tea. The tea garden, under at the foot of Mount Arjuna, has become one of the icons for Wisata Agro Wonosari, which is attractive for both foreign and local tourists to come and feel the cool air that does not exist in the hustle and bustle of the city. The promotion of Wisata Agro Wonosari is quite lacking because there is still lack of information about Wisata Agro Wonosari, so people's interest in visiting to Wisata Agro Wonosari is decreased. Therefore, the writer developed bilingual promotional booklets and websites to attract public interest and appeal again. This research aims to at creating a bilingual promotional booklet and website about Wisata Agro Wonosari. This final project uses the DDR (Design and Development Research) method. The writer uses Richey and Kelin's research types methodology, that is, DDR (Design and Development Research), which consist of several steps namely: analysis, design, development, implementation, and evaluation. Respondents of this study were visitors from Wisata Agro Wonosari. The two products that have been made, namely booklets and websites, have received positive responses from visitors.